Helimak control system. (1st April 2023) - Yang, S.Q.; Wen, F.; Wu, M.Q.; Li, H.; Zhu, X.; Hao, B.L.; Li, G.S.; Lin, X.D.; Gao, X.
Abstract: The excellent wall condition is essential for fusion devices to generate reproducible high-parameter plasma. Wall conditioning techniques should be validated before applying on large fusion devices to reduce potential risk. Helimak, a toroidal steady state magnetic confinement device, was reassembled and upgraded to a technical validation platform for wall conditioning. A new control system has been developed to achieve the upgrade of Helimak. The control system is based on a distributed control architecture, which provides not only efficient development but also flexible control mechanisms. For each auxiliary subsystem, a corresponding local control module is developed to drive and control a variety of equipment. The control network ensures real-time transmitting of the parameters and data. A dedicated trigger network and timing control module can improve synchronization and real-time performance. Data acquisition system based on mature commercial busses provides sufficient data acquisition capabilities for diagnostic tools. The data management system uses MDSplus to provide convenient data access. An independent interlock and safety system is designed for comprehensive and reliable personal protection. After engineering commissioning, the Helimak has realized wall conditioning by electron cyclotron resonance heating (ECRH) plasma at different resonance positions. The flexibility of control systems allows the installation of more wall conditioning tools in the future that will provide the ability to validate combined wall conditioning techniques. Helimak will become a low-cost, reliable technology verification platform, which will help to achieve advanced scenarios in tokamak and stellarator.